Alexithymia and asthma: a systematic review - Silvestro, Orlando; Ricciardi, Luisa; Catalano, Antonino; Vicario, Carmelo Mario; Tomaiuolo, Francesco; Pioggia, Giovanni; Squadrito, Giovanni; Schwarz, Peter; Gangemi, Sebastiano; Martino, Gabriella (Frontiers in Psychology, 2023)
Growing evidence from scientific research elucidates the important role of alexithymia in chronic-immune diseases. This review aims to explore the presence of alexithymia in patients affected by asthma and to clarify its associations with other involved psychological and physical factors. In January 2023, according to PRISMA guidelines, a systematic search using PubMed and Scopus, was conducted. Twenty-six studies were eligible based on inclusion criteria. Alexithymia was significantly present in asthma patients, with most studies reporting a higher prevalence (from 9% to 62.8%) compared to control groups (about 10%). Coexistence of asthma and alexithymia was associated with worse quality of life, psychiatric comorbidity, poor symptom control and difficulty in recognizing exacerbations of disease. These results suggest that alexithymia can negatively impact the management of asthma. For this reason, we recommend accuracy assessment in clinical settings and implementation of psychological interventions to promote emotional and physical well -being of asthmatic patients.